Problematika Hukum Tanah Absentee serta Dampak Pengecualian bagi Aparatur Sipil Negara terhadap Ketimpangan Agraria - Muhammad Rizqi; Nawang Wahyu Wulandari; Mitha Merlyan; Prawiradijaya (Tunas Agraria, 2026)
The main objective of agrarian reform in Indonesia is to achieve social welfare through equitable land distribution. This effort is mandated by Article 10 Paragraph (1) of Law No. 5 of 1960 (UUPA), which requires owners to actively cultivate agricultural land, and is reinforced by the prohibition of Absentee land ownership in Government Regulation No. 224 of 1961. However, the implementation of this policy has been ambivalent due to the exemption for civil servants through Government Regulation No. 4 of 1977. This study aims to analyze how this exemption has implications for agrarian inequality and how it relates to land conflicts in Indonesia. Using normative juridical methods and a legislative approach as well as case studies of court decisions, the results of this study show that the exemption for civil servants has created a new class of landlords that exacerbates structural inequality in land ownership. Based on data on agrarian conflicts, this exemption is often abused, which hinders land redistribution to small farmers. In terms of distributive justice theory, this policy is considered disproportionate because it prioritizes the economic security of state officials over the land sovereignty of local communities. This study recommends the need to revise Government Regulation No. 4 of 1977 and strengthen the digital land registration monitoring system to ensure that the social function of land is maintained and to close legal loopholes that perpetuate inequality.   Tujuan utama reforma agraria di Indonesia adalah mencapai kesejahteraan sosial melalui distribusi tanah yang berkeadilan. Upaya ini diamanatkan oleh Pasal 10 Ayat (1) UU No. 5 Tahun 1960 (UUPA) yang mewajibkan pemilik untuk mengusahakan tanah pertanian secara aktif serta dipertegas melalui larangan kepemilikan tanah secara Absentee dalam PP No. 224 Tahun 1961. Namun, implementasi kebijakan ini mengalami ambivalensi dengan adanya pengecualian bagi Aparatur Sipil Negara (ASN) melalui PP No. 4 Tahun 1977. Penelitian ini bertujuan untuk menganalisis bagaimana pengecualian tersebut berimplikasi pada ketimpangan agraria dan bagaimana hubungannya dengan konflik pertanahan di Indonesia. Dengan menggunakan metode yuridis normatif dan pendekatan perundang-undangan serta studi kasus putusan, hasil penelitian menunjukkan bahwa pengecualian bagi ASN telah menciptakan kelas tuan tanah baru yang memperparah ketimpangan struktur penguasaan lahan. Berdasarkan data konflik agraria, pengecualian ini sering kali disalahgunakan yang menghambat redistribusi tanah kepada petani kecil. Secara teori keadilan distributif, kebijakan ini dinilai tidak proporsional karena memprioritaskan jaminan ekonomi aparatur negara di atas kedaulatan lahan masyarakat lokal. Penelitian ini merekomendasikan perlunya revisi terhadap PP No. 4 Tahun 1977 dan penguatan sistem pengawasan pendaftaran tanah digital guna memastikan fungsi sosial tanah tetap terjaga dan menutup celah hukum yang melanggengkan ketimpangan.